(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The preschool education system prepares the foundation for the perfect development of children intellectually, mentally and aesthetically. During this period, the child’s multifaceted abilities, including artistic thinking, develop at a rapid pace. Artistic thinking serves as the basis for the child’s perception of being, the embodiment of real and imaginative images, the creation of new ideas. In turn, methodologies aimed at developing children’s artistic thinking significantly affect their aesthetic taste, figurative thinking and socio-cultural adaptation. Established experiments show that the methodology for the development of artistic thinking requires a specific approach, a multi-stage process and continuous search.